2018
DOI: 10.1074/mcp.ra118.000982
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Acetylation Levels Are Maintained During Acetyl-CoA Deficiency in Saccharomyces cerevisiae

Abstract: Nt-acetylation is a prevalent protein modification catalyzed by N-terminal acetyltransferases using acetyl-CoA as acetyl donor. Here, we performed a global analysis of Nt-acetylation in yeast following nutrient starvation. Contrary to histone acetylation, which is sensitive to acetyl-CoA levels, we demonstrate that Nt-acetylation remains largely unaffected to changes in cellular metabolism. We did, however, identify two protein groups that were differentially Nt-acetylated, one showing the same sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 86 publications
(124 reference statements)
6
35
0
Order By: Relevance
“…NatB mediated Ntacetylation is efficient, and nearly all proteins that code as NatB substrates are indeed NatB substrates, which is not true for other Nt-acetyltransferases. Interestingly, yeast NatB substrates are predominantly, near 100%, found in the acetylated state [28,29]. In line with these observations, we showed that Nma1 and Nma2 peptides identified from WT cells were 100% acetylated whereas Nma1 or Nma2 peptides identified from NatB mutants were 95%-100% non-acetylated [21].…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…NatB mediated Ntacetylation is efficient, and nearly all proteins that code as NatB substrates are indeed NatB substrates, which is not true for other Nt-acetyltransferases. Interestingly, yeast NatB substrates are predominantly, near 100%, found in the acetylated state [28,29]. In line with these observations, we showed that Nma1 and Nma2 peptides identified from WT cells were 100% acetylated whereas Nma1 or Nma2 peptides identified from NatB mutants were 95%-100% non-acetylated [21].…”
Section: Introductionsupporting
confidence: 84%
“…Nt-acetylation of Nma1 and Nma2 is likely important for mediating transient interactions or complex formation with proteins that either help protein folding or block key residues from being targeted by protein degradation machinery. This may help answer an interesting observation that in a normal cell Nma1, Nma2 and most other NatB substrates are always Nt-acetylated [21,29]. It is likely that non-acetylated populations of these proteins exist but are hard to identify because they are degraded before reaching maturity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…upon growth in glucose rich media. A recent study confirmed changed Nt-acetylation levels of Nat substrates in a protein-specific and not global manner under growth conditions conferring low acetyl-CoA levels (Varland et al, 2018). Overall, the selective effect on fewer protein targets (as compared to NatB) qualifies NatA to play a regulatory role in specific cell responses.…”
Section: Global Protein Aggregation Upon Lack Of Nt-acetylationmentioning
confidence: 88%